Improving higher-order thinking skill through POE (Predict, Observe, Explain) and guided discovery learning models - Witriyani Suryamiati; Adi Pasah Kahar; Anandita Eka Setiadi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
The low level of students’ higher-order thinking skills (HOTS) has been the main problem of education in Indonesia. This study aimed to determine the difference of students’ HOTS taught by using POE and Guided discovery learning models. This quasi-experimental research involved 34 students of X IPA 3 and 32 students of X IPA 4 at SMA Negeri 1 Sungai Ambawang-West Kalimantan as the sample. The data obtained by using test which was analyzed using Mann-Whitney U test. The results showed that the students’ HOTS who were treated with POE was significantly higher than those who were taught using Guided discovery learning. Therefore, it is suggested to implement POE to improve students’ HOTS.